High-Salt Diet Has a Certain Impact on Protein Digestion and Gut Microbiota: A Sequencing and Proteome Combined Study - Wang, Chao; Huang, Zixin; Yu, Kequan; Ding, Ruiling; Ye, Keping; Dai, Chen; Xu, Xinglian; Zhou, Guanghong; Li, Chunbao (Frontiers in Microbiology, 2017)
High-salt diet has been considered to cause health problems, but it is still less known how high-salt diet affects gut microbiota, protein digestion and passage in the digestive tract. In this study, C57BL/6J mice were fed low or high-salt diets (0.25% vs. 3.15% NaCl) for 8 weeks, and then gut contents and feces were collected. Fecal microbiota was identified by sequencing the V4 region of 16S ribosomal RNA gene. Proteins and digested products of duodenal, jejunal, caecal and colonic contents were identified by LC-MS-MS. The results indicated that the high-salt diet increased Firmicutes/Bacteroidetes ratio, the abundances of genera Lachnospiraceae and Ruminococcus (P< 0.05), but decreased the abundance of Lactobacillus (P< 0.05). LC-MS-MS revealed a dynamic change of proteins from the diet, host and gut microbiota alongside the digestive tract. For dietary proteins, high-salt diet seemed not influence its protein digestion and absorption. For host proteins, 20 proteins of lower abundance were identified in the high-salt diet group in duodenal contents, which were involved in digestive enzymes and pancreatic secretion. However, no significant differentially expressed proteins were detected in jejunal, caecal and colonic contents. For bacterial proteins, proteins secreted by gut microbiota were involved in energy metabolism, sodium transport and protein folding. Five proteins (cytidylate kinase, trigger factor, 6-phosphogluconate dehydrogenase, transporter and undecaprenyl-diphosphatase) had a higher abundance in the high-salt diet group than those in the low-salt group, while two proteins (acetylglutamate kinase and PBSX phage manganese-containing catalase) were over-expressed in the low-salt diet group than in the high-salt group. Consequently, high-salt diet may alter the composition of gut microbiota and has a certain impact on protein digestion.